An asymmetric allelic interaction drives allele transmission bias in interspecific rice hybrids - Yongyao Xie (Nature Portfolio, 2019)
Our limited understanding of the hybrid sterility (HS) mechanism in Asian–African rice hybrids hampers utilization of the interspecific heterosis for rice production. Here, the authors identify S1-mediated HS-related tripartite gamete killer-protector system, and explore their evolutionary relationship.